2016
DOI: 10.1093/comnet/cnw002
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the first case of the International Criminal Court from a network-science perspective

Abstract: This paper analyses the multi-level network composed of the legal decisions taken by the International Criminal Court since its creation in 2002. As many real-world networks, legal networks lend themselves to the use of graphs in which nodes represent the decisions taken by the Court and links stand for citations between decisions. Although useful, this framework does not account for the inherent complexity and hierarchy commonly observed in real data. In the context of legal networks in particular, interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 44 publications
1
17
0
1
Order By: Relevance
“…For a real life example, of the consequences that might occur after a single court decision we consider Ireland's drug loophole case 17 . Ireland's Court of Appeal found parts of the 1977 Misuse of Drugs Act to be unconstitutional 18 , since the act was added via ministerial order and without consulting the Oireachtas (both houses of the Irish parliament). After the Act was first passed, almost 40 years ago, successive amendments have added drugs to the original "banned" list.…”
Section: Resilience Of the Legislation Networkmentioning
confidence: 99%
“…For a real life example, of the consequences that might occur after a single court decision we consider Ireland's drug loophole case 17 . Ireland's Court of Appeal found parts of the 1977 Misuse of Drugs Act to be unconstitutional 18 , since the act was added via ministerial order and without consulting the Oireachtas (both houses of the Irish parliament). After the Act was first passed, almost 40 years ago, successive amendments have added drugs to the original "banned" list.…”
Section: Resilience Of the Legislation Networkmentioning
confidence: 99%
“…For example, Behn and Langford (2017) manually collected and coded roughly 800 cases on Investment Treaty Arbitration. Others have applied quantitative methods in the analysis of case law of the International Criminal Court (Holá et al 2012;Nollez-Goldbach 2014, 2015), the Court of Justice of the European Union (Lindholm and Derlén 2012;Derlén and Lindholm 2014;Tarissan and Nollez-Goldbach 2016;Derlén and Lindholm 2017a, b;Frankenreiter 2017a, b;Zhang et al 2017) or the European Court of Human Rights (Bruinsma and De Blois 1997;Bruinsma 2007;White and Boussiakou 2009;Christensen et al 2016;Olsen and Küçüksu 2017;Madsen 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also used this method to analyse case law of international courts. Some have performed a citation analysis of the case law of the CJEU (Lindholm and Derlén 2012;Derlén and Lindholm 2014;Tarissan and Nollez-Goldbach 2016;Derlén and Lindholm 2017a, b;Frankenreiter 2017aFrankenreiter , b, 2018. Derlén and Lindholm (2017a, p. 260) use this method to compare the precedential and persuasive power of key decisions of the CJEU using different centrality measurements.…”
mentioning
confidence: 99%
“…This induces a directed acyclic graph (DAG) on which one can rely to detect important legal decisions. Although recent, this approach has attracted considerable attention and has been applied to a series of jurisdictions [2]- [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the oft-used authority score, initially proposed by Kleinberg in the context of web searching [14], has been widely used to identify the landmark decisions and gain a general overview of the structure of the case law of individual courts. To further refine the analysis and develop dedicated metrics accounting for the moment at which the judgements are issued (that is, at the time when the cases are decided) Tarissan and Nollez-Goldbach in a more recent study [13], [15] proposed to rely on the temporal properties induced by the DAG structure. The study showed that this approach provides an alternative point of view of what is considered as an important decision through time and what can be labeled as rising star decisions that might become important reference points in the future.…”
Section: Introductionmentioning
confidence: 99%